Pemodelan Teknologi dalam Aplikasi KitaLulus untuk Lowongan Pekerjaan Menggunakan Metode Technology Acceptance Model (TAM) - Sugiyono; Hidayah, Vara Maulidyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Technological advancements have increased the need for job vacancy information, while the unemployment rate in Indonesia remains high. The KitaLulus application is designed to facilitate job seekers in finding opportunities that match their qualifications and preferences. This study adopts the Technology Acceptance Model (TAM) to analyze user acceptance of this application, focusing on perceived usefulness and perceived ease of use. The objective of this research is to evaluate users' perceptions of the KitaLulus application and analyze the influence of perceived usefulness, perceived ease of use, and behavioral intention on actual system usage. The results indicate that perceived usefulness and perceived ease of use significantly influence the acceptance and use of the KitaLulus application. These findings emphasize the importance of intuitive and beneficial application design to enhance technology adoption, while contributing to the development of job search applications and the academic literature on technology acceptance.